Calcaneus Fracture and Posterior Arthroscopic Primary Subtalar Arthrodesis (C-PASTA). Issue 3 (12th July 2022) - Martin, Kevin; Yoder, R. Garrett
Abstract : Background: Complex intra-articular calcaneal fractures often resulted in secondary pain and deformity, requiring subsequent subtalar arthrodesis 1 -3 . The literature suggests that primary subtalar arthrodesis in the acute period has good functional results 2, 3 . The literature also demonstrates that posterior arthroscopic subtalar arthrodesis for chronic arthritis has favorable results 5 . Thus, we propose an approach to treating these difficult intra-articular calcaneal fractures that utilizes a posterior arthroscopic primary subtalar arthrodesis technique—aptly named Calcaneus Fracture and Posterior Arthroscopic Primary Subtalar Arthrodesis (C-PASTA). Description: The procedure begins with the patient in the prone position. The subtalar joint is visualized with a 1.9-mm flexible camera through a standard posterior arthroscopic approach. With the help of the C-arm, position in the subtalar joint space is confirmed. The joint space is debrided with use of a 4-0 shaver and then prepared for arthrodesis arthroscopically with use of an osteotome and a burr. Next, we inject allograft demineralized matrix-based bone putty under direct arthroscopic visualization to fill residual gaps or defects. The arthrodesis is performed under fluoroscopic guidance with use of 2 guidewires followed by 2 to 3 titanium compression screws. The first screw is inserted along the posteromedial calcaneus and into the talar dome medially. The second is placed laterally into the head-neck junction of the talus. The third screw is placed distal to proximal from the plantar anterior process to the talar head. Finally, images are obtained in multiple views to ensure proper screw placement, and the screws are tightened sequentially to ensure equal compression across the joint. Alternatives: Nonoperative treatment of calcaneal fractures includes cast immobilization with non-weight-bearing, although this treatment is typically reserved for nondisplaced, small extra-articular fractures 6 . Operative treatment of calcaneal fractures includes open reduction and internal fixation, which is traditionally performed via a sinus tarsi approach or extensile lateral approach. Primary subtalar arthrodesis has been utilized primarily for Sanders type-IV fractures 6 . Rationale: Displaced intra-articular calcaneal fractures are associated with alarmingly high rates of posttraumatic arthritis (30% to 70% within 1 year of injury), and surgical outcomes are inversely proportional to the severity of the fracture pattern, with Sanders III and IV having the worst outcomes 1 . Treating these most severe fracture patterns with primary open subtalar arthrodesis has shown favorable results in terms of union rates, pain scores, and functional outcomes throughout the literature 2, 3 . However, some authors have reported rates of revision as high as 60% 4 . Thus, the PASTA procedure has been established, resulting in significantly better time to union, return to work, activities of daily living, and sports activities compared with open techniques 5 . Thus, given the favorable results of primary open subtalar arthrodesis and the proven results with use of an arthroscopic technique in the non-acute setting, we propose that C-PASTA can serve as an alternative treatment option in the acute setting for patients with Sanders type-III and IV calcaneal fractures. Expected Outcomes: We expect the outcomes of this procedure to mirror those found throughout the literature, which shows favorable results for open primary subtalar arthrodesis 1 -3 . With use of an arthroscopic approach, we expect better time to union, return to work, activities of daily living, and sports activities than if the procedure were performed in an open fashion 5 . In addition, minimizing soft-tissue damage through an arthroscopic approach may decrease the risk of infection and stimulate postoperative healing, perhaps accounting for the more favorable postoperative recovery period compared with an open procedure. Important Tips: In the arthroscopic approach to the subtalar joint, identify the flexor hallucis longus, making sure to stay lateral to that tendon to remain in the "safe zone." Utilizing the TRIMANO device (Arthrex) to distract the ankle longitudinally in addition to a solid bump placed on the anterior aspect of the ankle allows for optimal subtalar joint visualization. Fish-scaling with an osteotome followed by bone grafting allows for a good fill between cancellous fragments to stimulate an optimal environment for fusion. Divergent screws should be placed and tightened sequentially to ensure equal compression across the joint. Abbreviations and Acronyms: ADL's = activities of daily living CT = computed tomography SCD = sequential compression device AP = anteroposterior DVT = deep vein thrombosis BID = twice daily Vit = vitamin